The relationship among repeated sprint and change of direction abilities in football players with cerebral palsy - Henriquez, M. J.; Kokaly, M.; Herrera, F.; Reina, R. (Kinesiology, 2020)
This study aimed to describe and determine relationships between repeated sprint and change of direction abilities in football players with cerebral palsy according to four sport classes (FT5 to FT8). Seventeen male football players with cerebral palsy took part in this study (23.0±4.7 years, 65.9±9.5 kg, 168.8±5.9 cm). The repeated sprint ability (6×40-m sprints with a 20-second recovery) was evaluated to determine the best sprint time, mean sprint time, and percentage of sprint decrement. The difference in lactate concentration was determined using blood samples taken three minutes before and after testing. The Illinois Agility Test (IAT) was also used to assess players` change of direction ability. The FT8 players had better performance (p<.01) in the best sprint time, mean sprint time and in the IAT scores compared to the players of the sport classes FT5/6. Players of the sport class FT7 also reached higher performance in the IAT compared to the players of the sport classes FT5/6 (p<.05). A significant correlation was found between the best sprint time and mean sprint time (r=.94, p<.01), the best sprint time and the IAT (r=.62, p<.01), and between the best sprint time and the difference in lactate concentration (r=-.51, p<.05). The relationships between repeated sprint and change of direction abilities demonstrate the performance profile of para-footballers with cerebral palsy in those variables according to their sport classes, exhibiting lower performance than the values reported for regular football players.